Giant mesenteric lipoblastoma; a rare presentation of childhood abdominal mass - Ahmed Elrouby (Elsevier, 2022)
Lipoblastoma is a slowly growing benign tumor that arises from adipose tissue and diagnosed mostly below 3 years of life in the trunk (10%–60%), in the extremities (40%–45%) and rarely in the head and neck [1]We report a fifteen months old male patient who was presented to our institute with abdominal distension and short period of increasing dyspepsia. Abdominal exploration revealed a 15 × 15 cm freely mobile mesenteric lipoblastoma which was excised completely with the pathological examination confirming the diagnosis.